Looking for Synergies in Molecular Plasmonics through Hybrid Thermoresponsive Nanostructures - Nguyen, Mai; Felidj, Nordin; Mangeney, Claire (Chemistry of materials, 2016)
Gold nanoparticles (AuNPs) have been the subject of intensive work recently due to their outstanding optical, catalytic and electronic properties. Although the morphological characteristics (size and shape) of the AuNPs largely determine their properties, their functionalization or association to other materials play a primary role for optimizing their use in various applications such as drug delivery, theranostic, catalysis and (bio)sensing. Among the many possible options available by chemistry, the coupling of AuNPs with smart polymers is an exciting field offering the possibility to supply stimuli-responsive properties to the resulting nanocomposites. With regard to the photothermal properties of AuNPs, their combination with thermoresponsive polymers, such as poly(N-isopropylacrylamide) (PNIPAM) is particularly promising, likely to generate new synergies between the polymer component and the metallic nanoparticles. Despite such unique and intriguing advantages of AuNPs–PNIPAM nanocomposites, there is no exclusive review regarding this field at the interface between plasmonics and thermoresponsive polymers. To fill this gap, this review describes the general methods for preparing AuNPs–PNIPAM nanocomposites and their potential applications, highlighting the added-value properties emerging from the combination of AuNPs and PNIPAM in a single composite. New outlook for the near future to merge multiple functions at the nanometer scale and integrate building materials of various chemical nature (such as other stimulable polymers or the combination of AuNPs with other metals) into the same active plasmonic platform is described as well, emphasizing innovative approaches to improve their functionalities.